Mulheres camponesas e agroecologia: uma análise das relações de gênero no acampamento de reforma agrária herdeiros da terra de 1º de maio - Schneider, Clair Odete (2020)
Through this study, with peasant women who experiment and agroecology in the context of landreform, they aim to analyze how gender relations are linked to this experience at the Herdeiros da Terra Camp on May 1st. Aspects related to a family organization, a sexual division of labor and a hierarchy of activities were observed. A research was developed through participant observation and semi-structured interviews with women from agroecological groups that are part of or refer to the camp. In this sense, the results of this research produce reflections on the social roles played by women in the context of peasant agriculture, agrarian reform and agroecology. Throughout the research, women who participate actively in various MST activities, however, still prevail in the numbers of patterns of patriarchal practices in the daily life of the camp and the movement. Reflecting on these issues is necessary for the construction of new gender relations, respect, appreciation and visibility as activities performed by women, with no sense of recognition among farmers and workers and not just household chores, helpers or dependents of their parents or husbands.